Effectiveness of Biochar from Kapok Fruit Peel (Ceiba pentandra) for Decolorization of Indigosol Blue in Water - Iim E. Putra; Mery Napitupulu; Daud K. Walanda; Sitti Rahmawati (Universitas Tadulako, 2025)
In the batik industry, synthetic dyes such as indigosol blue are more commonly used than natural dyes. However, water pollution resulting from the batik industry is a serious issue that can threaten water quality and be harmful to human health. This research uses the adsorption method with kapok fruit peel as the adsorbent to address the problem of Indigosol blue dye. The kapok fruit peel is pyrolyzed at temperatures of 400 °C, 450 °C, and 500 °C. This study aims to determine the effectiveness of kapok fruit peel biochar in the adsorption of indigosol blue dye with variations in weight, time, and pH. The results show that the characteristics of kapok fruit shell biochar include moisture content at temperatures of 400 °C, 450 °C, and 500 °C, which are 7.40 %, 6.40 %, and 5.20 %, respectively. The ash content of kapok fruit shell biochar at temperatures of 400 °C, 450 °C, and 500 °C was 8.70 %, 6.10 %, and 5.40 %, respectively. The maximum weight of kapok fruit shell biochar in absorbingindigosol blue dye was 75 mg with an adsorption capacity of 0.986 mg/g. The maximum contact time required was 40 minutes with an adsorption capacity of 0.626 mg/g. The maximum pH of indigosol blue dye in the adsorption process occurred at pH 7 with an adsorption capacity of 1.709 mg/g. These findings indicate that kapok fruit shell biochar has potential as an environmentally friendly alternative adsorbent for treating batik industry wastewater.